Arctic regions [electronic resource] : voyage to Davis' Strait - Duncan, David, fl. 1827. (London : Printed by E. Billing, for the author, 1827)
Half title: Voyage to Davis' Strait. "Sailed from London 3rd April, 1826 ." " --- Our infant Winter sinks ." "Entered at Stationer's Hall." "Dedicated by permission of His Royal Highness the Duke of Clarence." Electronic reproduction. Mode of access: Internet. 44